Frontispiece: Long‐Lived Charge‐Transfer State in Spiro Compact Electron Donor–Acceptor Dyads Based on Pyromellitimide‐Derived Rhodamine: Charge Transfer Dynamics and Electron Spin Polarization. Issue 33 (8th August 2022) - Chen, Xi; Sukhanov, Andrey A.; Yan, Yuxin; Bese, Damla; Bese, Cagri; Zhao, Jianzhang; Voronkova, Violeta K.; Barbon, Antonio; Yaglioglu, Halime Gul
Abstract : Electron Transfer . In their Research Article (e202203758 ), Jianzhang Zhao et al. investigate the long‐lived charge‐transfer state in spiro donor–acceptor dyads based on pyromellitimide‐derived rhodamine.